Study on Etiology and Maternal Complications of Intrauterine Fetal Death - Malik, Adiba; Begum, Tahera; Noor, Serajun (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2019)
Background : Management of pregnancy with good fetal and maternal outcome is a challenge to the obstetrician which can be achieved by screening the risk factors of Intra Uterine Fetal Death (IUFD) and thereby prevent, control and treat them by quality preconceptional and antenatal care. Materials and methods: This cross-sectional study, done in a tertiary care hospital during a period of two years where 100 pregnant women with history of intrauterine fetal death were included after informed written consent. Intrauterine fetal death was confirmed by Ultrasonogram. Different risk factors and maternal complications were observed. Then data was analyzed with the help of SPSS-20. Results: Among 100 women, maximum patients were aggregated between age group 26-35 years (45%) and next to which was 16-25 years (35%) primipara was 32% and multipara was 31%. Regarding Antenatal care (ANC) 32% patients attended two antenatal visits and 28 % patients had no antenatal visits and 18% patients completed > 5 visits. Regarding causes of IUFD, 34% due to hypertension in pregnancy, 14% mother was severely anemic, 13% mother had Diabetes Mellitus (DM) abruptio placenta was found in 15% mother, maternal gastroenteritis 05%, maternal fever 09%, cord accident 3% and in 19% cases no causes were identified. Regarding maternal complications, blood transfusion needed in 28% patients, PPH occurred in 12% patients, Sepsis 08%, caesarean section needed in 07 % cases, ARF 4%, DIC in 03% cases and maternal mortality 01%. Mean ± SD of total hospital stay was 4 ± 1.5 days. Conclusion: There are different risk factors of IUFD which if identified earlier,then by treating the correctable etiologies, recurrence of IUFD and its related maternal complications can be prevented or reduced. Chatt Maa Shi Hosp Med Coll J; Vol.18 (1); Jan 2019; Page 23-26